High expression of L-type amino acid transporter 1 (LAT1) predicts poor prognosis in pancreatic ductal adenocarcinomas. Issue 11 (19th July 2012) - Yanagisawa, Nobuyuki; Ichinoe, Masaaki; Mikami, Tetuo; Nakada, Norihiro; Hana, Kiyomi; Koizumi, Wasaburo; Endou, Hitoshi; Okayasu, Isao
Abstract : Background and aims: Molecular target therapy against L-type amino acid transporter 1 (LAT1) is unique and expected to be developed soon. LAT1 expression was investigated in pancreatic cancer as a prognostic predictor. Methods: Surgically resected pancreatic ductal adenocarcinomas (PDAC, n=66) were investigated using immunohistochemistry. For reference, intraductal papillary mucinous carcinomas (IPMC, including intraductal papillary mucinous neoplasm (IPMN) with high-grade dysplasia or with an associated invasive carcinoma, n=13) and adenomas (IPMA, including IPMN with low- and intermediate-grade dysplasia, n=5) were also examined. Results: LAT1 expression scores increased from PDAC to IPMA to IPMC. Kaplan–Meier analysis showed significant differences between LAT1-high and -low scores in PDAC. Even in each Ki-67-labelling index (LI) low and high PDAC group (cut off 40%), high LAT1 expression could also predict poor prognosis. Multivariable analysis showed that LAT1 expression, Ki-67 LI, tumour differentiation and size were individual prognostic factors. Conclusions: LAT1 aberrant overexpression in PDAC predicts poor prognosis, independent of Ki-67 LI, and offers a potential target for future anticancer therapy with its inhibitors.